When Anna realises that it is Coronation day she starts singing and fantasising about meeting "the one". Then she starts dancing with a head and accidentally lets go and throws the head across the room onto a cake.
If Anna is at point ( 5 , 0 ) on the cartesian co-ordinate plane and the cake is at ( − 3 , 0 ) , the flight path of the head can be described by the equation:
y = − 2 x 2 + b x + c
Find the value of b + c
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
That was terribly trivial. Why won't you use Vieta's formula since the y value are both zero for x=-5 and x=3 (this shows that -5 and 3 are the roots of the equation)?
Log in to reply
whoops forgot that.... :P
yeah......I did it the same way.....
Yan Yau, you should tell Mr. Street to use this problem in class - it's related to coordinate geometry xD
Log in to reply
@Aashman Vyas Yes, our class "learnt" co-geo. but > 4 3 doesn't know what a parabola is and the rest doesn't know how to graph one.... thats how screwed up our class is.....
Frozen :D
I solved this problem in this way.
Why can't you just use the intercept form and expand it?
Slightly different from @Yan Yau Cheng :
First, for a parabola in the form a x 2 + b x + c , the axis of symmetry will always vertical. This means that given any two x coordinates, the axis of symmetry will always be defined as x = 2 x 1 + x 2 where x 1 and x 2 are the x -coordinates of two (not necessarily distinct) points sharing a common y coordinate. Thus, we can average 5 and − 3 to find the axis of symmetry, which is thus x = 1 . Now, we know that the formula for the axis of symmetry for a parabola is simply 2 a − b . Substituting, we get 1 = 4 b ⟹ b = 4 .
Now, we can plug this in and solve for c . Let's use ( 5 , 0 ) . Thus, − 2 ( 2 5 ) + 4 ( 5 ) + c = 0 and c = 3 0 . We can easily verify that this is also true for the point ( − 3 , 0 ) . Thus our desired answer is 3 0 + 4 = 3 4 . Great problem Yan Yau! :D
Big story simple problem!LOLSimply put in those points, they would satisfy the equations!
Simply substitute values for x and y. Get a pair of linear equations.Solve them.Easy !!
Put y=0 to get a Quadratic equation in x it will be -2x^2+bx+c=0 Let the two roots be x1,x2 which are -3,5 Also x1+x2=b/2 x1*x2=(-2/c) Solve to get B=4 C=30
Problem Loading...
Note Loading...
Set Loading...
Substitute ( 5 , 0 ) and ( − 3 , 0 ) into the equation:
we have:
0 = − 2 ( 5 ) 2 + 5 b + c 0 = − 2 ( − 3 ) 2 − 3 b + c
Combining the 2 equations:
− 2 ( 5 ) 2 + 5 b + c = − 2 ( − 3 ) 2 − 3 b + c − 5 0 + 5 b = − 1 8 − 3 b 8 b = 3 2 b = 4
Substitute b = 4 into the first equation:
0 = − 2 ( 5 ) 2 + 5 ( 4 ) + c c = 3 0
Hence b + c = 4 + 3 0 = 3 4